The Potential of Local Tubers as Nutritious Instant Food - I Gede Yoga Ayuning Kirtanayasa; I Nengah Muliarta (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2021)
This literature study aims to find out and explore the potential of local tubers as nutritious instant food. Instant food is food that is packaged, easy to prepare, practical, or treated only. The food is generally produced by the food processing industry with high technology and provides a variety of additives to preserve and provide flavor to the product. Nowadays people's consumption patterns are required to be fast-paced due to increasingly dynamic work, so instant food is the solution, but not all instant foods are good for health. Tubers are one of the commodities that have the potential to be developed as instant food, in addition to being a substitute for rice to support food diversification programs. Food diversification is a way to organize or create a diversity of commodities consumed, with the program of diversification of food, it is expected that people's consumption patterns not only depend on one type of food but also have other alternatives.